Demonstrasi Pijat Oketani Untuk Kelancaran Produksi ASI Di Kabupaten Bulukumba - Husnul Khatimah; Sumarni; Isnaeny; Kurniati Akhfar; Rika (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2025)
Exclusive breastfeeding during the first six months of a baby's life is essential to support optimal growth and development. However, the achievement of exclusive breastfeeding targets in Indonesia is still low due to various obstacles, such as suboptimal breast milk production, inappropriate breastfeeding techniques, and minimal education for postpartum mothers. One non-pharmacological intervention that has proven effective in increasing breast milk production is the Oketani massage technique, a gentle breast massage method developed in Japan. This community service activity aims to provide Oketani massage education and training to fifteen postpartum mothers in Paenre Lompoe Village, Gantarang District, Bulukumba Regency. The implementation method includes counseling, massage technique demonstrations, direct practice, and pre-post test evaluations. The results of the activity showed an increase in participant knowledge and the practical benefits of Oketani massage in facilitating breast milk. In addition to increasing breast milk production, this massage also has positive psychological impacts, such as reducing stress and strengthening the mother-child bond. With an educational and participatory approach, this activity is expected to increase breastfeeding success and strengthen the role of families and communities in supporting maternal and infant health.